Analisis Kelayakan Bisnis Like Mie And Coffee Di Batang - Alfiesyah, Emilia; Abadi, Muhammad Taufiq (BISMA : Business and Management Journal, 2023)
Marketing mix is a collection of marketing variables that are carried out in an integrated manner or a marketing strategy that is carried out simultaneously by the company to pursue the desired sales target in the target market. The research method used in this study uses a qualitative descriptive method. The variables used by Like Mie and Coffee companies include product, place, price, and promotion. The materials used in the manufacture of products are of good quality. It has a strategic and instagramable place. The prices offered are very affordable and provide lots of discounts. In promoting its products using print media and social media, Like Mie and Coffee is a business that deserves to be developed from all aspects that have been carried out by the company. Apart from that, establishing a second branch in Semarang is proof that the business is very feasible to develop.